mbasaka – A Web 2.0 Initiative in the Indian Higher Education Sector - Bharel, Sunny Gaurav (2009)
mbasaka is a unique Web 2.0 initiative that aims to tackle the problem of quality higher education in India (especially for the MBA) by aiding learning amongst students through its array of subscription and ad-revenue based online streaming lecture videos by professional lecturers and professors. The growing need for quality education in India, the lack of government infrastructure and the easy reach of the internet have created the perfect environment for mbasaka to be born.